Oral leukoplakia: A potentially malignant oral lesion (Research, Society and Development, 2023)
Introduction: Leukoplakia is essentially a clinical term for white lesions with potential malignancy. Its diagnosis is made both by clinical aspects and by eliminating other similar lesions. Case report: Patient C.I.O., 49 years old, sought the clinic of the Faculty of Dentistry of the Federal University of Alagoas, complaining of painless lesions in the region of the lip mucosa, hard and soft palate, and reported using homemade cigarettes. A biopsy of the lesions was performed, confirming the diagnosis of oral leukoplakia. Methodology: A search was carried out in the Google Scholar, PubMed and Medline databases, using the terms “Oral leukoplakia”, “Biopsy”, “Oral neoplasms” and “Mouth Mucosa”. Objective: The objective of this work is to report the case of a patient with leukoplakia manifesting in oral cavity. Results and discussion: Clinically, they can be homogeneous or non-homogeneous lesions and, histologically, the distinction can be made by the presence of dysplasia and its different degrees. Most chronic injuries develop in response to trauma and may be asymptomatic. Treatment consists of eliminating the cause, monitoring it and using medication, if necessary. Final considerations: Therefore, it is important to search and correct interpretation of lesions to avoid risk of malignancy.